Engineering fundamentals & problem solving - Eide, Arvid R. (McGraw Hill Education, 2018)
Presents a complete introduction into the engineering field. This text helps students develop the skills needed to solve open-ended problems in SI and customary units while presenting solutions in a logical manner. It introduces subject areas common to engineering disciplines, that require the application of fundamental engineering concepts